Магнітопружне деформування тіла із порожниною - Лавінський, Денис Володимирович (НТУ "ХПІ", 2016)
Розглядається задача магнітопружного деформування тіла нескінченних розмірів із порожниною за рахунок магнітострикції, яке знаходиться у стаціонарному однорідному магнітному полі. Наведена математична постановка задачі. В якості чисельного методу обрано метод скінчених елементів. Одержані результати, щодо розподілу тензорних компонент, які описують процес деформування. Порівняння чисельних результатів в околі порожнини із результатами аналітичного розв'язку, дозволили зробити висновок про можливість застосування методу скінчених елементів для аналізу магнітопружного деформування тіл із неоднорідністю структури.

We consider the problem of magneto-elastic deformation of an infinite size body with the cavity due to magnetostriction. A ferromagnetic body is placed in a stationary homogeneous magnetic field. Mathematical formulation of the problem is presented. The finite element method was chosen as the numerical method for the analysis of the distribution of the vector component of the electromagnetic field and the tensor component of the deformation process. The results, which illustrate the distribution of the tensor component of the forming process, were obtained. Comparison of the numerical results in the vicinity of the cavity with the results of analytical solutions allowed us to conclude about the possibility of using the finite element method for the analysis of magneto-elastic deformation of bodies with heterogeneity of structure.
Magnetoelastic deformation of a body with a cavity
Keywords: електромагнітне поле; магнітопружне деформування; магнітострикція; метод скінчених елементів; electromagnetic field; magneto-elastic deformation; magnetostriction; finite element method